Use of the Glasgow Coma Scale for Decision of Life Threatening Injury in Cases of Intoxication - Keskin, Rabiş; Yorulmaz, Coşkun; Yavuz, Mehmet Sunay; Aşırdizer, Mahmut (The Bulletin of Legal Medicine, 2001)
Mortality risk in intoxications is assessed on the basis of the following criteria: intensive care, duration of the stay in the ICU, antidote therapy and results of the drug assay, if present. Glasgow Coma Scale (GCS) is a useful diagnostic tool for the assessment of cerebral functions in patients with craniocerebral trauma and is correlated with the mortality. The present study aims to discuss the applicability of GCS in cases of intoxication. Intoxication cases referred to the 5th Specialty Committee of the Council of Forensic Medicine in the years 1999-2000 were evaluated retrospectively based on the criteria of GCS. Mortality risk assessment was requested in 359 among 647 cases of intoxication,. We evaluated 30 cases fitting the criteria of GCS. The remaining cases could not be assessed due ter inappropriate medical records. Based on our study we think that a modified GCS for intoxication cases should be implied in all health institutions. Key words: Glasgow coma scale, life threatening injury, entoxication.